War, aggression and self-defence - Stemmet, André (Scientia Militaria - South African Journal of Military Studies, 2020)
This review is written against the background of the continuing Syrian conflict, and specifically Operation Peace Spring, the Turkish military intervention in northern Syria ostensibly aimed at creating a safe zone there for the resettlement of Syrian refugees present on Turkish territory. In terms of international law, the legality of this Turkish action has been analysed in some detail by a number of commentators and analysts in the popular media and on academic websites and blogs, illustrating that the branch of international law known as the jus ad bellum – the law with respect to the legality of war – remains one of the most dynamic and interesting fields of international law and international relations.